Human-like Computers: A Lesson in Absurdity - Velden, Manfred (Schwabe Verlag, 2021)
Some 50 years ago, the computer scientist Joseph Weizenbaum found that the idea that the socialization of a machine might in any way be comparable to the one of a human, is a sign of the madness of our time. Today, the idea is mostly not seen as a mad but rather as a quite plausible one, as are many other ideas about human-likeness of computers, like them having consciousness. At a closer look, however, the alleged human-likeness of computers is merely derived from weak analogies, like them having intelligence just because they can play chess (and nothing else). The book details the psychological and physiological preconditions for human mental functions to occur, ones that cannot possibly be fulfilled by computers. It puts the computers-as-humans issue into the broader philosophical frame of the scientistic view that man is basically a machine.